Browning of White Adipocytes in Fat Grafts Associated With Higher Level of Necrosis and Type 2 Macrophage Recruitment. (30th March 2021) - Liu, Tong; Fu, Su; Wang, Qian; Cheng, Hao; Mu, Dali; Luan, Jie
Abstract: Background: Induced browning adipocytes were assumed less viable and more prone to necrosis for their hypermetabolic property. A previous study showed that browning of adipocytes was more evident in fat grafts with necrosis in humans. Objectives: The authors aimed to estimate whether fat transfer–induced browning biogenesis was associated with necrosis and its potential inflammation mechanisms in murine models. Methods: Human subcutaneous adipose from thigh or abdomen of 5 patients via liposuction was injected in 100 µL or 500 µL (n = 20 per group) into the dorsal flank of 6- to 8-week-old female nude mice fed with normal chow diet and harvested after 2, 4, 8, and 12 weeks. Control groups did not receive any grafting procedures (sham operation), where lipoaspirates were analyzed immediately after harvest. Histology and electronic microscopy, immunological analyses of browning markers, necrosis marker, and type I/II macrophages markers in mice were performed. Results: Histology and electronic microscopy showed browning adipocytes in fat grafts with a higher level of necrosis (0.435 ± 0.017 pg/mL for cleaved caspase-3, ** P < 0.01), IL-6 (749.0 ± 134.1 pg/mL, *** P < 0.001) and infiltration of type 2 macrophage profiles in mice (twofold increase, * P < 0.05). Conclusions: Browning of adipocytes induced by fat transfer in mice is in parallel with post-grafting necrotic levels associated with elevated interleukin-6 and activated type 2 macrophage profiles, which promote browning development.